Soil ameliorants alter physicochemical properties and fungal communities in saline-sodic soils of Northeast China. Issue 8 (3rd July 2019) - Wang, Shaojie; Luo, Shasha; Zhou, Xue; Chang, Chunling; Tian, Lei; Li, Xiujun; Yu, Hailing; Gao, Qiang; Tian, Chunjie
ABSTRACT: To understand the mechanisms of soil ameliorants affecting microbial communities is important for saline-sodic soils reclamation. High-throughput sequencing was used to characterize the fungal community in soils amended with four types of ameliorants over an 8-year period. Besides a control without any additional ameliorant (CK), other four treatments including 1) amendment with sandy soil (SS), 2) amendment with desulfurization gypsum (DG), 3) amendment with farm manure (FM), and 4) amendment with a mixture of SS, DG, and FM (M) were analyzed. Soil pH and electrical conductivity significantly decreased with the addition of soil ameliorants, whereas the soil organic carbon (SOC), total nitrogen (TN), and SOC/TN ratio (C/N) significantly increased in the FM and M treatments compared with the CK treatment. Fungal richness increased significantly with the mixed ameliorants addition (M). Distinct fungal community structures were observed in the treatments with soil ameliorants. The fungal community composition was significantly associated with the SOC, C/N, aggregate content with a diameter > 0.25 mm and geometric mean diameter. The changes in these soil characteristics were highly correlated with the ameliorants additions, suggesting that the impacts of ameliorants on the soil fungal community occurred indirectly as a result of alterations to soil physiochemical properties.